Paving the way for integrated STEAM-H education in agricultural product processing vocational high school - Ai Tusi Fatimah; Agus Yuniawan Isyanto; Toto Toto; Bibin Bintang Andriana (Jurnal Pendidikan Vokasi, 2023)
The increasing boundaries of agriculture and health disciplines in STEM to STEAM-H (Science, Technology, Engineering, Agriculture, Mathematics, and Health) is an opportunity for the world of education to expand integration between disciplines for solving increasingly challenging and complex problems. The Agricultural Product Processing Program, one of the spectrums of vocational education in Indonesia that focuses on agriculture, is located in the STEAM-H area. Therefore, this study aims to explore cross-subject connections, essential concepts, and teacher beliefs to implement integrated learning. This study used a qualitative approach with a case study design. Data were collected through interviews and documents. Participants were teachers at SMK Agrotechnology Processing Agricultural Products in Ciamis, Indonesia. Descriptive analysis was carried out on the standard subject matter of agribusiness, mathematics, and science to obtain an overview of interdisciplinary connections in STEAM-H and the essential concepts within it. The findings of this study are that mathematics and science have a role in processing agricultural products subject, as indicated by the existence of conceptual connections in them. Concepts of processing products of agriculture become conceptual and contextual integrators of science and mathematics. The essential concepts of mathematics and science are either explicit or implicit, within or outside the secondary school curriculum set by the government. Based on the participants' beliefs, integrated STEAM-H in learning can be carried out at agribusiness vocational schools. This finding has implications for integrated STEAM-H learning planning that requires further research.